Mild cognitive impairment and its management in older people - Eshkoor SA (Dove Medical Press, 2015)
Sima Ataollahi Eshkoor, Tengku Aizan Hamid, Chan Yoke Mun, Chee Kyun Ng Institute of Gerontology, Universiti Putra Malaysia, Selangor, Malaysia Abstract: Mild cognitive impairment (MCI) is a common condition in the elderly. It is characterized by deterioration of memory, attention, and cognitive function that is beyond what is expected based on age and educational level. MCI does not interfere significantly with individuals’ daily activities. It can act as a transitional level of evolving dementia with a range of conversion of 10%–15% per year. Thus, it is crucial to protect older people against MCI and developing dementia. The preventive interventions and appropriate treatments should improve cognitive performance, and retard or prevent progressive deficits. The avoidance of toxins, reduction of stress, prevention of somatic diseases, implementation of mental and physical exercises, as well as the use of dietary compounds like antioxidants and supplements can be protective against MCI. The modification of risk factors such as stopping smoking, as well as the treatment of deficiency in vitamins and hormones by correcting behaviors and lifestyle, can prevent cognitive decline in the elderly. The progressive increase in the growth rate of the elderly population can enhance the rate of MCI all over the world. There is no exact cure for MCI and dementia; therefore, further studies are needed in the future to determine causes of MCI and risk factors of progression from MCI to dementia. This will help to find better ways for prevention and treatment of cognitive impairment worldwide. Keywords: AD, Alzheimer’s disease, cognition, dementia, MCI